Efficacy and compliance of vulvovaginal candidiasis therapy during pregnancy - Kan N.E; Lomova N.A; Kokoeva D.N (LCC «Medicine-Inform», 2018)
Efficacy and compliance of vulvovaginal candidiasis therapy during pregnancy Tyutyunnik V.L., Khan N.E., Lomova N.A., Kokoeva D.N. National Medical Research Center for Obstetrics, Gynecology and Perinatology named after Academician V.I. Kulakov, Moscow Vulvovaginal candidiasis is an inflammatory change in the vaginal mucosa caused by a fungal infection due to a significant weakening of the immune system. Vulvovaginal candidiasis occupies one of the leading places among infectious pathologies of the lower segment of the genital tract. A significant prevalence of this pathology is proved by the fact that almost 75% of women experience at least one episode of candidal infection during their lifetime, and in 45% of cases it becomes a disease. Vulvovaginal candidiasis is recorded in 60% of pregnant women. It is more often diagnosed in the first and third trimester, when the hormonal and immune systems undergo significant changes. Recently, the complex preparation Primafungin® has been widely and effectively used from the second trimester of pregnancy. A prospective, randomized blind study of 60 pregnant women with vulvovaginal candidiasis established a reliable efficacy of Primafungin®, confirmed by the positive dynamics of clinical signs and laboratory results. The use of natamycin-containing drugs in the therapy of vulvovaginal candidiasis during pregnancy is highly effective and has no side effects. Key words: vulvovaginal candidiasis, pregnancy, therapy, natamycin. For citation: Tyutyunnik V.L., Khan N.E., Lomova N.A., Kokoeva D.N. Efficacy and compliance of vulvovaginal candidiasis therapy during pregnancy // RMJ. 2018. № 2(I). P. 54-58.